PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATERI OPERASI HITUNG PERKALIAN PADA SISWA KELAS IV - Roni Hamdani, Acep; Rohayati, Rohayati (STKIP Subang, 2017)
This research is based on the low understanding of the concept of Mathematics students in learning Mathematics material of multiplication operation in SD Negeri Nugraha Pelita. The problem is caused by the learning process that is still using conventional methods. This makes learning tends to be boring and students find it difficult to understand the learning materials that have been delivered, so that the impact of student understanding is likely to be low. Student Teams Achievement Division (STAD) cooperative learning model is very effective to be used as solution to solve the learning problem that happened during this time. The method used in this research is PTK method (Classroom Action Research). The subject of this research is the fourth grade students of SD Negeri Nugraha Pelita in the academic year 2017/2018 with the number of 33 people. Based on the results of learning and research analysis it can be concluded that the model of cooperative learning type Student Teams Achievement Division (STAD) can improve students' learning comprehension on Mathematics subjects of multiply counting operations in the fourth grade of SD Negeri Nugraha Pelita.